The Face and Content Validity of the Persian Version of Occupational Identity Questionnaire in People With Multiple Sclerosis - Mahya Eshghi; Malahat Akbarfahimi; Ghorban Taghizadeh Hajlouee; Elahe Hojati Abed (Function and Disability Journal)
Background and Objectives: Occupational identity (OI) is a crucial factor in occupational therapy evaluations and interventions which is not investigated in chronic conditions, including multiple sclerosis (MS). The Occupatinal Identity Questionnaire (OIQ) is an appropriate tool for assessing occupational identity. As a result, this research aims to adapt the Persian version of OIQ for people with MS and evaluate its face and content validity. Methods: The face validity of OIQ was qualitatively and quantitatively evaluated with 15 participants diagnosed with MS. Interviews were used to qualitatively assess the face validity. In addition, the item impact method (IIM) was applied to quantitatively assess face validity. A total of 12 experts with experience in the field of neurology participated in evaluating content validity. The content validity ratio (CVR) and the content validity index (CVI) were applied in this evaluation. Results: All the items received IIM scores above 1.5 (3.03 to 4.62). Also, none of the items were mentioned as incomprehensible during interviews. The CVR scores for each item ranged from 0.63 to 1 (based on Lawshe >0.59). After that stage, a CVI study was conducted. In that study, scores for each item ranged from 0.83 to 1. S-CVI/Ave score was 0.94 and scale CVI/universal agreement (S-CVI/UA) was 0.57. Based on experts’ comments, it was determined that adjustments were necessary for item number 6 and 10. Conclusion: The Persian version of the OIQ demonstrates acceptable face and content validity in the context of MS. It is recommended to conduct a test re-test, internal consistency, construct validity, and factor analysis.